Quantification and comparison of the impact of the smoking status on oral polymorphonuclear leukocyte and malondialdehyde levels in individuals with chronic periodontitis: A double-blinded longitudinal interventional study - Ninad Milind Padhye; Ashvini Mukul Padhye; Himani Swatantrakumar Gupta (Wolters Kluwer Medknow Publications, 2019)
Background: The formation of reactive oxygen species by oral polymorphonuclear leukocytes (oPMNs) is amplified in smokers with chronic periodontitis (CP) causing tissue damage which can be measured by quantifying levels of malondialdehyde (MDA). Objective: To quantify and compare the impact of smoking status on oPMN and MDA in individuals with CP before and after scaling and root planing (SRP). Materials and Methods: Sixty individuals were divided into four groups, namely, periodontally healthy (Group A), current smokers with CP (Group B), former smokers with CP (Group C), and nonsmokers with CP (Group D). Parameters assessed were bleeding on probing (BOP), gingival index (GI), probing pocket depth (PPD), clinical attachment level, gingival recession, periodontal inflamed surface area, salivary MDA, and oPMN at baseline and 6 and 12 weeks after SRP. Results: Increased PPD (P = 0.01) and decreased GI (P = 0.021) was noted in Group B as compared to C and D at baseline. Periodontal intervention caused a greater resolution of inflammation in Groups C and D as compared to B as noted from the GI and BOP. A reduction in MDA (P = 0.074) was noted in Groups C and D as compared to B, and oPMN levels were higher (P = 0.009) in Group C and D as compared to B. Conclusion: Greater periodontal destruction is seen in current smokers than former and nonsmokers with CP. MDA can be considered as a reliable biomarker for oxidative stress as it directly correlates with the oPMN levels.